2013
DOI: 10.3389/fimmu.2013.00475
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Exhaustion as a Mechanism to Protect Against Severe Immunopathology and Death from an Overwhelming CD8 T Cell Response

Abstract: The balance between protective immunity and immunopathology often determines the fate of the virus-infected host. How rapidly virus is cleared is a function of initial viral load, viral replication rate, and efficiency of the immune response. Here, we demonstrate, with three different inocula of lymphocytic choriomeningitis virus (LCMV), how the race between virus replication and T cell responses can result in different disease outcomes. A low dose of LCMV generated efficient CD8 T effector cells, which cleare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 32 publications
7
109
0
Order By: Relevance
“…Such an adjustment in combination with persisting expression of PD-1 could be of vital importance in chronic infections 64,65 . In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 96%
“…Such an adjustment in combination with persisting expression of PD-1 could be of vital importance in chronic infections 64,65 . In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 96%
“…Finally, when the ability to sustain exhausted CD8 + T cell populations is compromised, all containment of chronic infection can be lost 12 . In settings of chronic infection where immunopathology can occur, T cell exhaustion may serve as a mechanism to protect against tissue damage 139 . In this context, one might envision that for viruses that cannot be fully eradicated, at least containing these pathogens to low levels might be the evolutionary driver of T cell exhaustion.…”
Section: Figurementioning
confidence: 99%
“…However, even though there is no single transcription factor that serves as an exhaustion determining factor, both exhausted CD8 + and CD4 + T cells have a distinct molecular profile from that of effector and memory T cells and share a core set of transcription factors such as B-lymphocyte–induced maturation protein 1, basic leucine zipper transcription factor, activating transcription factor (ATF)-like and Helios [14 ▪▪ ]. Moreover, recent studies suggested that CD8 + T-cell exhaustion maybe a stable and heritable state of differentiation representing functional adaptation of the T cells to protect the host from excessive immunopathology and at the same time provide some control of viral replication [15 ▪ ,16,17 ▪▪ ,18]. Regardless of what the ultimate terminology will be for this phenomenon, it is clear that under certain conditions the T cells progressively lose proliferative and effector capabilities that are up to a certain point reversible.…”
Section: T-cell Exhaustion: a Terminally Differentiated State Or Revementioning
confidence: 99%
“…An interesting recent study [18] demonstrated that three different inocula of lymphocytic choriomeningitis virus (LCMV) result in different disease outcomes. A low dose of LCMV generated efficient CD8 + T effector cells, which cleared the virus with minimal lung and liver lesions.…”
Section: Factors Affecting T-cell Exhaustionmentioning
confidence: 99%